The effectiveness of Fibraurea tinctoria as anticancer properties: A literature review - Nabila Fatihah Raihana; A’immatul Fauziyah (Poltekkes Kemenkes Aceh, 2025)
Background: Cancer remains a leading cause of mortality globally, necessitating the exploration of natural compounds for therapeutic interventions. Fibraurea tinctoria Lour (FT), an indigenous herb in Asia, has shown potential anticancer properties, but its efficacy and mechanisms require further elucidation.Objectives: This review aims to synthesize existing literature on FT's anticancer effects, focusing on its bioactive components, mechanisms of action, and the quantitative impact of FT extracts on various cancer cell lines.Methods: A systematic literature search was conducted using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria across databases including Google Scholar, PubMed, and ScienceDirect, yielding six eligible studies from an initial pool of 321. These studies assessed both in vitro and in vivo effects, differing in extract types, dosages, and treatment durations.Results: FT extracts exhibited notable antitumor effects, with palmatine hydrochloride (PaH) demonstrating significant inhibitory activity against cancer cell proliferation. Quantitative data indicate that FT extracts can reduce cancer cell viability by 28-82.79%, with PaH-PDT emerging as a promising therapeutic strategy, effectively inducing apoptosis in multiple cancer cell lines.Conclusion: FT extracts possess substantial anticancer potential, primarily through mechanisms involving DNA damage and apoptosis induction.